Making the transition from on-campus to online learning : Pre-service teachers' experiences of online learning as a result of COVID-19. - Muir, Tracey; Livy, Sharyn; Murphy, Carol; Trimble, Allison (Journal of University Teaching & Learning Practice v.19 n.5 https://doi.org/10.53761/1.19.5.3, 2022)
Online learning is rapidly becoming the preferred study option for many higher education students, due to its accessibility, convenience and flexible teaching arrangements. For other students who have access to a university campus, their preferred option is to attend on-campus classes, where advantages include synchronous interaction with peers, lecturers and access to practical experiences, materials, and resources. The impact of COVID-19 resulted in interruptions to social, economic, cultural, and educational life, with social distancing measures and health and well-being concerns leading to widespread restrictions in numerous different contexts. Universities throughout Australia restricted access to campuses and shifted their teaching of classes to purely online delivery. This shift posed many challenges for students and staff as ways of teaching and learning were reconceptualised. This paper examines the experiences of two different cohorts of pre-service teachers from two different universities who were studying full-time on-campus at the time when the restrictions were applied and reports the impact the shift to online had on cognitive, social and teaching presence within a model of community of inquiry. The findings indicate that despite the challenges involved with the rapid transition to online delivery, participants were able to identify the presence of core elements of the model, and how these factors impacted upon their engagement with the course. [Author abstract]